Reflective practice programme for registered nurses in training hospitals in Windhoek - N. Nelumbu, Lucia (International Journal of Advanced Nursing Studies, 2015)
Problems or incidents occurring in clinical settings are often seen as indicators of poor nursing care and even indicators of a lack of reflective practice skills. A qualitative, explorative, phenomenological, descriptive and contextual approach was conducted to explore and describe how reflective practice is practised by registered nurses in training hospitals in Windhoek. The findings revealed inadequate knowledge of reflective practice among registered nurses. Based on these findings the educational programme was developed to facilitate learning and application of reflective practice in clinical practice. This paper presents the description of an educational programme that was developed to facilitate learning and practice of reflective practice by registered nurses to make a difference to their patients’ care.